Umedalen Skulptur 95. - Galleri Stefan Andersson, Umea (Umea : Umedalens skulpturpark, 1995)
Balka, Miroslaw ; Bäckström, Barbro ; Caldeborg, Mats ; Cronqvist, Lena ; Englund, Lars ; Eriksson, Tina ; Erlandson, Anna ; Gormley, Antony ; Graham, Dan ; Gunnars, Carina ; Hake, Claes ; Hansson, Ronny ; Kapoor, Anish ; Kirschenbaum, Bernard ; Krüger, Anders ; Naraha, Takashi ; Nilsson, Jörgen ; Persson, Karin ; Róbertsdóttir, Ragna ; Rollof, Ulf ; Rückriem, Ulrich ; Valinger, Lars ; Öberg, Charlotte
biografie
Umedalen Skulptur 95, Umedalens skulpturpark, Umea, 10/6 - 11/9/1995
Zweeds
kunstcatalogus
Keywords: Umea